Effective working hours and wages: the case of downward adjustment via paid absenteeism - Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
This paper compares contractual with effective working hours and wages, respectively. Effective working hours are defined as contractual working hours minus absent working hours. This approach takes into account workers' downward adjustment of working time via paid absenteeism if working time constraints are present, which induce workers to accept contracts with larger than their optimal choice of working hours. A German personnel data set, which contains precise information on wages as well as working and absence hours, is used to assess the impact of such downward adjustment on wage inequality and wage differentials (gender, schooling, age).
Keywords: J22; J31; 330; Absenteeism; earnings; inequality; wage differentials; working hours